THE DIFFICULTIES NATIONALIZATION OF THE TURNIQUETTE - Batistti Archer, Cleber (2021)
The idea of creating a completely national tourniquet arose from the difficulty of having access to tourniquets in our country. All existing models are produced abroad and only one or two models are legally marketed in our country. Not to mention other models that are sold in Brazil, which are copies and of poor quality, putting the lives of the victim and the operator at risk.